A Critical Exposition of Plato’s Philosophy of Social Stratifications in Ensuring Justice - Mita, Jannatul Ferdous (Philosophy and Progress, 2024)
This article descends into Plato’s representation of justice in The Republic, focusing on exploring a notion that has been fundamental to society since its inception. While justice was formed to ensure equality within a stratified society, it frequently results in inequity for particular sectors of society. This paradoxical element of justice makes it biased and sometimes fictitious for some groups of people. An unfortunate consequence of pursuing justice is that specific segments of society are regularly deprived. Therefore, this article discusses the essence of social stratification in Plato’s concept of justice and how far this stratification does justice for each class. Philosophy and Progress, Vol#73-74; No#1-2; Jan-Dec 2023 P 241-257